Per- and poly-fluoroalkyl substances: A review of sources, properties, chromatographic detection, and toxicological implications - Eliasu Issaka; Mabruk Adams; Enock Adjei Agyekum; Josephine Baffoe; Blessing Tornyeava (AIMS Environmental Science)
Emerging per and poly-fluoroalkyl substances (PFASs) are very resistant to degradation and have negative impacts on human and environmental health at very low concentrations. The initial stage in removing PFASs from contaminated locations is their detection and quantification. Particularly utilized in this context are Gas Chromatography-Mass Spectrometry (GC-MS), Liquid Chromatography-Tandem Mass Spectrometry (LC-MS/MS), and High-Performance Liquid Chromatography (HPLC). In this review, we seek to contribute to our understanding of the state-of-the-art in emerging PFAS by offering a complete analysis of PFAS in environments, taking into consideration their sources, classes, and properties. Polyfluoroalkyl ether substances (PFAES), short-chain PFA, replacement PFA, and fluorotelomer-based substances can bioaccumulate in living species, making their detection even more necessary. We intend to provide researchers with an overview of the current state of research on PFASs in environments, encompassing the toxicological effects and their detection and quantification methods, serving as a guide for current and future studies.